The Effect of Motion Analysis (Coachview) Application on the Understanding and Skills of Basic Kicking and Punching Techniques in Pencak Silat in Grade Vii Students at SMPN 2 Sumenep - Jaya Abadi Amroin; Yoso Wiyarno; Hayati Hayati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the effect of using the motion analysis application CoachView on students' understanding and skills in basic punching and kicking techniques in pencak silat among seventh-grade students at SMPN 2 Sumenep. The background of this research lies in the low levels of understanding and performance of students in pencak silat, which is still taught through conventional methods. Therefore, there is a need for innovative technology-based learning media. This study employed a true experimental method with a Pretest-Posttest Control Group Design. The sample consisted of two randomly selected classes, each with 32 students, divided into an experimental group (using CoachView) and a control group (conventional learning). The research instruments included a skill performance test and a comprehension questionnaire on basic pencak silat techniques. The results showed a significant improvement in both comprehension and skill performance in the experimental group. The average posttest score for technical skills was notably higher than that of the control group. The t-test analysis indicated a significance value of less than 0.05, confirming a statistically significant effect of CoachView usage. Furthermore, the validity and reliability tests of the instruments showed that all instruments were valid and highly reliable (α = 0.882 for the questionnaire and α = 0.910 for the skill rubric). In conclusion, the use of the CoachView application is effective in enhancing students' understanding and technical skills in pencak silat. This technology provides clear visual feedback and enables students to identify and correct movement errors independently. The study recommends the integration of CoachView as an alternative learning media in physical education classes.